Theological women's studies in southern Europe = Theologische Frauenforschung in Südeuropa - Ferrari Schiefer, Valeria 1954-; Valerio, Adriana 1952-; Berlis, Angela 1962-; Bieberstein, Sabine 1962- (Leuven [u.a.] Peeters, 2005)
This volume with its emphasis on "Southern Europe" is devoted now for the second time to theological research by women in a particular region of Europe. Women doing research in France, Italy, Spain and Greece provide evidence of and reflection on the history of women's theological studies in their countries and present the results of their studies. These reveal an impressive spectrum of theological research which sometimes has been and must be conducted in difficult structural contexts and under very different economic conditions. This makes the vitality of the research presented all the more convincing; in the different contexts of the individual countries it demonstrates specific and very varied emphases in academic theory and method. Precisely because of their complex and diverse points of departure, the articles evidence a fundamental, interdisciplinary approach and a creative way of seeing things which is concerned to ensure a fundamental openness for debate and dialogue. This volume thus provides an insight into the fascinating diversity and complexity of theological research in Europe.
Literaturverz. S. 177 - 196
Bd. 13 u.d.Gesamttitel: Journal of the European Society of Women in Theological Research
Beitr. teilw. dt., teilw. engl., teilw. franz.
Keywords: Women in the Catholic Church -- Europe, Southern; Feminist Theology -- Europe, Southern; Aufsatzsammlung